2022
DOI: 10.3389/fphar.2022.842717
|View full text |Cite
|
Sign up to set email alerts
|

OAT10/SLC22A13 Acts as a Renal Urate Re-Absorber: Clinico-Genetic and Functional Analyses With Pharmacological Impacts

Abstract: Dysfunctional missense variant of organic anion transporter 10 (OAT10/SLC22A13), rs117371763 (c.1129C>T; p.R377C), is associated with a lower susceptibility to gout. OAT10 is a urate transporter; however, its physiological role in urate handling remains unclear. We hypothesized that OAT10 could be a renal urate re-absorber that will be a new molecular target of urate-lowering therapy like urate transporter 1 (URAT1, a physiologically-important well-known renal urate re-absorber) and aimed to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…A plausible explanation for this point would be that URAT1 but not GLUT9 might have backup machinery. Indeed, recent studies revealed that like URAT1, organic anion transporter 10 (also known as SLC22A13) has a physiological role as a renal urate re-absorber expressed on the apical side of renal proximal tubular cells though its contribution on renal urate handling is smaller than that of URAT1 ( Higashino et al, 2020 ; Toyoda et al, 2022 ). By contrast, on the basal side of the cells, no physiologically-important urate transporters have been identified to date, except for GLUT9.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation for this point would be that URAT1 but not GLUT9 might have backup machinery. Indeed, recent studies revealed that like URAT1, organic anion transporter 10 (also known as SLC22A13) has a physiological role as a renal urate re-absorber expressed on the apical side of renal proximal tubular cells though its contribution on renal urate handling is smaller than that of URAT1 ( Higashino et al, 2020 ; Toyoda et al, 2022 ). By contrast, on the basal side of the cells, no physiologically-important urate transporters have been identified to date, except for GLUT9.…”
Section: Discussionmentioning
confidence: 99%
“…The Michaelis-Menten constant (K m ) and maximal velocity (V max ) of the SVCT1-or Svct1-mediated urate transport were determined by fitting the Michaelis-Menten model to experimental urate transport rates and concentrations using nonlinear regression curve fitting in GraphPad Prism 8 (GraphPad Software, San Diego, CA, USA), as described previously [49].…”
Section: Calculation Of the Kinetic Parameters And Half-maximal Inhib...mentioning
confidence: 99%
“…The SVCT1-mediated transport activities were expressed as a percentage of the control (100%). Using the least-squares method with Excel 2019 (Microsoft, Redmond, WA, USA), fitting curves were obtained based on the calculated values according to the following formula as described previously [49]:…”
Section: Calculation Of the Kinetic Parameters And Half-maximal Inhib...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that dysfunctional missense mutation of SLC22A13 gene reduced SUA levels and the risk of gout. Meta-analysis displayed that rs117371763 (R377C) variant of SLC22A13 gene has significant anti-gout effect [ 56 ]. It is certain that SLC22A13 , like SLC22A12 , can provide effective targets for the treatment of gout.…”
Section: Introductionmentioning
confidence: 99%